Efficacy and safety of indomethacin 0.1% eye drops compared with ketorolac 0.5% eye drops in the management of ocular inflammation after cataract surgery - Weber, Michel; Kodjikian, Laurent; Kruse, Friedrich; Zagorski, Zbigniew; Allaire, Catherine M. (Acta Ophthalmologica, 2013)
Purpose: To determine whether indomethacin 0.1% eye drops are at least as effective as ketorolac 0.5% eye drops in treating ocular inflammation following cataract surgery. Methods: Prospective, multicenter, investigator-masked, parallel-group, randomized, active-controlled clinical trial. Cataract patients were randomized in a 1:1 ratio to receive indomethacin or ketorolac administered QID for 3 weeks beginning 1 day before surgery. The primary end-point was aqueous flare measured by laser flare meter at postoperative Days 1 and 7. Secondary end-points included retinal thickness, slit lamp and funduscopic examinations and postsurgical pain ratings. Safety and tolerability were also assessed. Results: A total of 86 patients were included in the per protocol population (n = 43 per treatment group). Indomethacin was found non-inferior to ketorolac for comparison of aqueous flare at postoperative Days 1 and 7 (Day 1: 95% CI: -2.37, 5.50; non-inferiority upper margin, 15 ph/ms and Day 7: 95% CI: -7.83, -0.94; non-inferiority upper margin, 8 ph/ms) and statistically better than ketorolac at Day 7 (p = 0.013). There were no significant between-group differences in aqueous flare and change from baseline in retinal thickness at postoperative Days 30 and 90. Indomethacin showed a higher subjective tolerance rating than ketorolac at postoperative Days 7 and 30 (p <= 0.044). Conclusion: Indomethacin 0.1% was at least as effective as ketorolac 0.5% at Day 1 and more effective than ketorolac 0.5% at Day 7 in treating ocular inflammation after uncomplicated cataract surgery. Indomethacin was better tolerated than ketorolac. There were no clinically meaningful safety concerns with either treatment.
EVALuna2:21108